Analisis Efektivitas Safety Management System (SMS) dalam Menurunkan Angka Kecelakan Kerja di Engine Room - Priyanto; M. Ikhsan Rizki Dinata (Politeknik bumi Akpelni, 2025)
The engine room of a merchant ship is one of the work areas with the highest accident risk on board, due to limited environmental conditions, the heat of the engine room affecting the room temperature, and complex operational systems. This study aims to improve the effectiveness of the implementation of the Safety Management System (SMS) and the crew's understanding of safety in reducing the number of work accidents in the engine room based on a recent literature review. Using a qualitative approach through a literature review, this study examines scientific documents, maritime safety reports, and international regulations such as the ISM Code. The results of the study indicate that the implementation of a structured Safety Management System through crew training, standard operating procedures (SOP), an incident reporting system, and internal audits can reduce the rate of work accidents in the engine room. The implementation of the Safety Management System still faces challenges, such as the crew's poor understanding of procedures, language limitations, and a weak safety culture. This study recommends strengthening visual-based training, regular evaluations, and the use of digital technology for safety reporting and monitoring. These findings are expected to provide academic and practical contributions in supporting maritime work safety, particularly in the engine room of merchant ships.